Da obra projectada à obra vivida. Sobre o conjunto habitacional da Bouça - Maria de Freitas de Sousa Camps (2012)
The present work is a reflection on the issue of appropriation of space in the Housing Bouça by those who inhabit it, with particular attention to the common outdoor spaces. The architectural work is here understood as an organism composed of two distinct and complementary dimensions: the work planned (their physical and material) and experienced work (fruit of the society to which it belongs).